2004
DOI: 10.5012/bkcs.2004.25.6.934
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Optical Characteristics of CdS/Ag Metal-Semiconductor Composite Quantum Dots

Abstract: There have been great interests in the optical, electrical, and chemical properties of quantized nanoparticles, such as semiconductor quantum dots (QDs).1 Semiconductor QD structures particularly have attracted attentions because of their strong three dimensional quantum confinement effects. Researches have been held to develop better methods to fabricate such semiconductor QDs, showing great progress during the past decade. One of the most early developed fabrication methods is to embed II-VI semiconductor co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 17 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Qdots coated with a noble metal have been shown to exhibit coupling between the plasmon resonance from the metal and the quantum size effect of the Qdots that give rise to new properties. Jeang et al reported a red-shift of the exciton absorption peak for the Ag/CdS nanocomposite [86]. Je et al investigated the local field-induced optical properties of CdS/Ag core/shell nanocomposites [87].…”
Section: Structure Of Quantum Dotsmentioning
confidence: 99%
“…Qdots coated with a noble metal have been shown to exhibit coupling between the plasmon resonance from the metal and the quantum size effect of the Qdots that give rise to new properties. Jeang et al reported a red-shift of the exciton absorption peak for the Ag/CdS nanocomposite [86]. Je et al investigated the local field-induced optical properties of CdS/Ag core/shell nanocomposites [87].…”
Section: Structure Of Quantum Dotsmentioning
confidence: 99%